Group Norms as Moderator in The Effect of Cross Group Friendship on Outgroup Attitude: A Study on Interreligious Group in Indonesia - Yustisia, Whinda (UI Scholars Hub, 2021)
Past studies indicate that the effect of intergroup contact on outgroup attitude is not isolated to contextual factors. One of the contextual factors that has begun to be studied is group norm. However, group norm in these studies is still merely conceptualized as the perception of how ingroup members evaluate outgroup members. In fact, according to norm focus theory, in a given context, individuals are influenced, at least, by two types of group norms, namely injunctive norms (i.e., what most people morally accept to do) and descriptive norms (i.e., what most people do). To fill the gap, present studies attempt to answer the question of how two types of group norms might have different effects on the relationship of intergroup contact and outgroup attitude. Built on past studies, it was hypothesized that both quality (H1) and quantity (H2) of cross-group friendship would positively affect outgroup attitude. Further, built on the fact that the nature of attitude in present studies is more utilitarian than hedonic, it was predicted that injunctive norms would be more likely to function as moderator in the effect of cross-group friendship on outgroup attitude, either in dimensions of quality (H3) or quantity (H4). 110 Muslim students were recruited as participants and asked to fill in a self-report questionnaire regarding their interactions with Christians. The findings partly support the hypotheses.